2016
DOI: 10.1097/ajp.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Pain at Hospital Discharge Following Traumatic Orthopedic Injury

Abstract: Objectives The purpose of this study was to determine whether pain at hospital discharge is associated with general health and depression and post-traumatic stress disorder (PTSD) at 1 year following traumatic orthopaedic injury. Methods This study prospectively enrolled 213 patients, 19 to 86 years of age, admitted to an Academic Level 1 trauma center for surgical treatment of a traumatic lower-extremity or upper-extremity orthopaedic injury. Pain at hospital discharge was measured with the Brief Pain Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 54 publications
(70 reference statements)
2
41
0
Order By: Relevance
“…We found that 65% of the patients reported severe pain (mean NRS 6) shortly after ICU discharge. This is similar to a follow‐up study in orthopaedic patients reporting an average pain intensity (BPI of 6.3 [SD 2.4]), with 44% of the patients having severe pain in the past 24 hours (NRS ≥ 7) before hospital discharge. Furthermore, a higher pain interference score in the ward was associated with a higher PTSS‐10 score.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found that 65% of the patients reported severe pain (mean NRS 6) shortly after ICU discharge. This is similar to a follow‐up study in orthopaedic patients reporting an average pain intensity (BPI of 6.3 [SD 2.4]), with 44% of the patients having severe pain in the past 24 hours (NRS ≥ 7) before hospital discharge. Furthermore, a higher pain interference score in the ward was associated with a higher PTSS‐10 score.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, a higher pain interference score in the ward was associated with a higher PTSS‐10 score. Archer et al found, in orthopaedic patients, using the Clinical‐Administered PTSD Scale and Mississippi PTSD Scale significant correlations between pain and PTSD at hospital discharge and after 1 year. To the best of our knowledge, our study is the first to measure pain in a general ICU population in the ward shortly after ICU discharge, and the amount of patients reporting pain and the association between pain and PTS symptoms/PTSD warrant further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, by definition pain comprises psychological elements (IASP, 1994), thereby suggesting that, in part, analgesia depends on them. The extant literature demonstrates that psycho-pathology is both an antecedent (Gerrits, van Marwijk, van Oppen, van der Horst, & Penninx, 2015) and a consequence of persistent pain (Archer et al, 2016). Extending the scope beyond formal psychopathology, psychological factors that are known to influence pain and analgesia include cognition (Burns, Glenn, Bruehl, Harden, & Lofland, 2003; Darnall et al, 2017; Salomons, Moayedi, Erpelding, & Davis, 2014; Seminowicz & Davis, 2006; Seminowicz et al, 2013; Ziadni, Sturgeon, et al, 2018), emotion (Burns et al, 2015; McCracken & Keogh, 2009; Vlaeyen, Crombez, & Linton, 2016), appraisal (Ziadni, Sturgeon, et al, 2018), expectations (Atlas et al, 2012; Colloca & Miller, 2011b; Palermo & Drotar, 1996; Wager, Atlas, Leotti, & Rilling, 2011), attention (Kucyi, Salomons, & Davis, 2013; Seminowicz & Davis, 2006), beliefs about pain and its treatment (Carriere, Martel, Kao, Sullivan, & Darnall, 2017; Carriere et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Discharge pain scores can be identified as an outcome for discharge. There are other implications of poor pain control on discharge from the hospital identified such as long-term depression and PTSD [22]. Pain must be controlled in the hospital to prevent the development of chronic pain out of the hospital.…”
Section: Discussionmentioning
confidence: 99%